The impact of a training curriculum for the tolerance of using (training mask) in some functional indicators for the 400 meters and 800 meters for the junior class - أ.م.د. طارق احمد ميرزا (physical education and sport sciences college for women/ Baghdad University, 2018)
The aim of the study is to prepare a training curriculum using a training mask, to identify the effect of the curriculum prepared in the special endurance and some functional indicators in the 400 m and 800 m range of beginners, as well as to identify the differences in the results of the post tests of the functional indicators between the 400 m and 800 m, The researcher used the experimental method in the comparison method for the two experimental groups to suit the nature of the research. The sample of the research was the Peshmerga Club of Athletics. The activity ran 400 meters and 800 meters, the youth class (15-17 years) for the season (2018-2019) Runners make up a percentage of (100%) of the community (800 meters). The sample of the research (10) was chosen as a runner representing (83.33%) of the total research community. They were divided into two groups, such as the experimental group The first (5) runners of 400 meters running, which were applied to the training curriculum for the endurance using (Training Mask 2.0), while the second experimental group (5) runners to run 800 meters, who applied the same curriculum, and applied the vocabulary of this The curriculum on the two experimental groups, three days a week (Saturday, Sunday, Wednesday), for (8) weeks in the period of special preparation, The total number of units of training (24) units, and after the tests of the dimension of the researcher reached the following conclusions: The results showed significant differences between the results of tribal and remote tests and for the benefit of remote tests in the two groups (Rakmi 400 meters and 800 meters for the junior group), the training program The results of the tests of the two groups showed no significant differences between the results of the 400 meters and 800 meters for the beginners category. The results showed that there were no significant differences between the results of the two groups running 400 meters and 800 meters for the beginners group. The results showed that there is a clear impact of the training curriculum used in the development of special endurance, which led to the raising of the level of the sample and reflected this development in the tests of dimension.